A glaciotectonic landform in the Shyok valley, Trans-Himalayan Karakoram Range, India - Abdul Qayoom Paul; Harish Bahuguna; Parveen Kumar (Journal of Glaciology)
This study reports and discusses the first case of glaciotectonic landforms in the Shyok valley of the Trans-Himalayan Karakoram Range, Ladakh, where a large decomposed granite megablock (8.2 km2) along with underlying diamicton is thrust over the unconsolidated Quaternary glaciofluvial sediments along a fault gouge zone near the village of Khalsar. The absence of deformation signatures below the fault gouge indicates that the brittle fault acted as a décollement surface under frozen conditions along which the glaciotectonic megablock was translated. The other deformation features include slickensides, ductile shear, thrust propagation fold noses, clastic dykes and rafts of granite and slate within the diamicton sediments. These features indicate a subglacial glaciotectonic nappe origin of the landform. The presence of juxtaposed brittle to ductile deformation fabric, clastic dykes and the superimposition of deformed decomposed granite and diamicton over the undisturbed fluvial sediments indicates a permafrost glacial margin and proglacial environment under sufficient subglacial hydrodynamic conditions for the entrapment and transportation of the glaciotectonic megablock. The deformation fabric consistently shows a southeast orientation, indicating an advancing glacier motion from northwest to southeast. The Siachen Glacier which formerly flowed down the Nubra valley is the most likely cause of the Khalsar glaciotectonic landform.